Isolation of Novel 6-methylideneoxecane-3,4,5,7,8,9-hexol from the Leaves of Rauwolfia vomitoria, Apocynaceae - Owaba, Azibanasamesa D.C; Rafiu, Raji O.; Frank, Arueniobebh; Eboh, Darlington D.; Bunu, Samuel J. (Biology, Medicine, & Natural Product Chemistry, 2024)
Rauwolfia vomitoria (Wennberg) belongs to the family Apocynaceae, the dried leaves were extracted successively using n-hexane, dichloromethane, and 70% methanol, concentrated in vacuo. Extracts were subjected to antibacterial assay and the butanol fraction was subjected to chromatographic purification to obtain NBF12 which was subjected to spectral analysis. The antibacterial of n-Hexane, dichloromethane, and 70% methanol extracts was inactive against the screened organisms assessed (Staphylococcus aureus, Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa). NBF12 is yellowish crystals (10.5 mg), Rf (0.69), UV, max Abs (248) The carbon 13C-NMR spectrum displayed ten carbon atoms; one methylene, two methylene oxide carbon, 6-carbinolic carbon (Sp3) and a quaternary carbon (SP2). The spectrum showed a tertiary carbon at Î´131.09 ppm, due to C-6 and at Î´ 114.74 ppm due to exocyclic methylidene carbon (Sp2) (C=CH2) linked to the C-6position. Based on the spectral data NBF12 is 6-methylideneoxecane-3,4,5,7,8,9-hexol with a molecular formula C10H18O7, molecular weight 250 g/mol.